Refractory linings thermomechanical design and applications - Schacht, Charles A. (Mechanical engineering (Marcel Dekker, Inc.), 1995)
This work describes the technology necessary to optimize the performance of any refractory lining. It provides an overview of the thermomechanical behaviour and wear of refractory lining systems, and details the structural behaviour of several classical refractory geometries, highlighting the critical regions of each lining system where high stress is most likely to create fractures.